The antibacterial effects of hylocereus polyrhizus fruit extracts against selected bacteria / Nur Dayana Hassan Cheong, Abdul Fatah Hasan Kashfi and Hartini Yusof - Hassan Cheong, Nur Dayana; Hasan Kashfi, Abdul Fatah; Yusof, Hartini (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
In recent years, the growing number and active spread of antibiotic resistance have become a major concern globally. This forces the need to discover, analyse and develop new kinds of antibiotics, especially among plants. There are still limited data on the extracts from Hylocereus polyrhizus fruit as antimicrobials. In this study, the disc diffusion and broth-microdilution methods are used to investigate the antimicrobial activity of methanol and ethanol extracts of Hylocereus polyrhizus flesh towards selected bacteria (Staphylococcus epidermidis, Staphylococcus aureus, Proteus mirabilis, Bacillus cereus, Pseudomonas aeruginosa, and Escherichia coli). The methanolic extract possesses better antimicrobial properties. The methanolic extract of H. polyrhizus showed significant antimicrobial activities against all Gram-positive bacteria, and one of the Gram-negative bacteria, which is better compared to ethanolic extract. The range of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) are 125mg/mL to 250mg/mL. In conclusion, this study shows that H. polyrhizus could be used as an alternative for the pre-existing antimicrobial agent.